PlayPhrase.Me: A multimedia corpus for foreign language education - Ibrahim Halil Topal (Technology in Language Teaching & Learning)
Technological advancements have not only introduced new tools for language education but also tailored apps and resources for specific language skills. These include mobile apps (e.g., Drops: Language Learning Games for vocabulary), websites (e.g., SpanishDict for Spanish dictionary and grammar), and reference tools (e.g., Grammarly for writing assistance). One such resource is PlayPhrase.me, an online and mobile tool serving as a database of movie clips for language practice, particularly vocabulary. Despite the relative attention similar tools (e.g., YouGlish and Voscreen) have received, only two studies were conducted about the PlayPhrase.me a website. Accordingly, there is a need for a review that outlines its general characteristics and pedagogical affordances. To this end, this review evaluated the website and revealed considerable potential for vocabulary, grammar, and pronunciation learning. Citing the possible pitfalls, such as short video durations, lack of filtering, and absence of evaluative and competitive means, the researcher offered recommendations for improvement. The review concludes with the researcher’s reflections as a teacher and urges further research to validate the findings.